2013
DOI: 10.1002/da.22219
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Enhance in Vivo Exposure-Based Therapy of Spider Phobia

Abstract: These findings indicate that adding cortisol to in vivo exposure-based group therapy of spider phobia enhances treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 39 publications
9
68
1
Order By: Relevance
“…We utilized fMRI to record the neural activity in response to pictures of spiders in patients with spider phobia, who received either cortisol or placebo, and in control subjects who did not receive any medication. As shown in previous studies (Aerni et al, 2004;Soravia et al, 2014), cortisol treatment improves phobic symptoms, but patients still exhibits a significant level of phobic response. To investigate neural correlates of residual symptoms, we compared the phobic patient groups with the healthy controls.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…We utilized fMRI to record the neural activity in response to pictures of spiders in patients with spider phobia, who received either cortisol or placebo, and in control subjects who did not receive any medication. As shown in previous studies (Aerni et al, 2004;Soravia et al, 2014), cortisol treatment improves phobic symptoms, but patients still exhibits a significant level of phobic response. To investigate neural correlates of residual symptoms, we compared the phobic patient groups with the healthy controls.…”
Section: Introductionsupporting
confidence: 68%
“…The patients were selected from a cohort of our previous clinical trial, investigating the effectiveness of cortisol treatment and cognitive behavioral therapy on spider phobia treatment (Soravia et al, 2014;clinicaltrials.gov NCT01574014). The subjects were recruited via advertisement.…”
Section: Subjectsmentioning
confidence: 99%
“…Repeated or prolonged unreinforced retrievals can lead to extinction learning (Merlo et al, 2014; but see Cai et al (2006) for single-trial extinction). GCs and stress have been shown to enhance exposure-based psychotherapy (de Quervain et al, 2011;Soravia et al, 2006;Soravia et al, 2014) and extinction learning (Hamacher-Dang et al, 2013), presumably by enhancing the consolidation of the newly acquired extinction memory (de Quervain and Margraf, 2008). In their rodents fear conditioning study, Cai et al (2006) demonstrated that postreactivation corticosterone can impair recall of established contextual fear memory, presumably through enhancement of extinction learning, even after a single trial.…”
Section: Discussionmentioning
confidence: 99%
“…16 Indeed, stress and associated elevated cortisol levels increase extinction memory consolidation, 59 and the administration of glucocorticoids enhances the effects of exposure therapy for anxiety disorders. 60, 61, 62 Accordingly, FKBP5 genotype might influence the initial fear memory strength as well as the process of extinction learning.…”
Section: Discussionmentioning
confidence: 99%